Pengaruh Penggunaan Media Elektronik Terhadap Motivasi Belajar Siswa Kelas X BKP SMK Negeri 1 Bireuen - San'ani (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
Teachers as educators must be able to use the right learning media so that the desired learning objectives can be achieved. One of the learning media that is widely used is electronic media. The purpose of this study was to increase students' learning motivation in drawing regular pentagons by knowing one side and in a circle in class X BKP SMK Negeri 1 Bireuen through electronic media. The research was carried out for 3 months. The research subjects were students of class X BKP SMK Negeri 1 Bireuen for the 2016/2017 academic year. The number of students in class X BKP is 39 male students. The data obtained came from class X BKP students of SMK Negeri 1 Bireuen and teachers/collaborators who were collaborators in carrying out this research activity. Based on this research, it can be concluded that using Electronic Media can increase learning motivation for Basic Building Drawing subjects, especially the basic competence of Drawing Regular pentagons by knowing one side and in a circle for class X BKP students at SMK Negeri 1 Bireuen. 2016/2017 Academic Year. At the end of the first cycle, students who achieved complete learning were 46% (18 children), and 54% students who had not completed (21 children), while at the end of the second cycle, 92% (36 children) and 8% (3 children) have not achieved mastery learning. With an average grade of 67.07 for the first cycle and 83.79 for the second cycle. Meanwhile, in the initial conditions, the students' average score was 61.23 and only 23% of students completed. the results of non-test observations of the learning process showed changes in students being more active during the learning process